A Review of Scott E. Page's The Difference: How the Power of Diversity Creates Better Groups, Firms, Schools, and Societies - Ioannides, Yannis M (Journal of Economic Literature, 2010)
This assessment of Scott Page's The Difference (Princeton University Press, 2007) emphasizes the depth and breadth of the book's coverage and arguments and checks them against existing empirical evidence, when available. It argues that the book navigates artfully between being a “manifesto” for diversity and rigorous science writing while at the same time marketing economic science in new ways. The review welcomes the book's popularization of richer aspects of everyday decision making, individual and collective, and its making an excellent case for the social significance of abstract economic theorizing, especially about problem solving. It praises the book's lively interpretations of statistical tools of decision making by means of enticing narratives. The book's rhetoric urges us to move beyond accepting diversity as a matter of taste, or even because of its beneficial effects on the “production function,” and ultimately adopts its powerful logic. It speculates that the book's true impact will likely come after thorough empirical research. In empirical endeavors, issues of definition, especially of identity and of measurement, and evaluation of policies that would enhance diversity would be decisive. In democratic societies, policies may pose new dilemmas as they benefit from public interest in overcoming the accumulation of past disadvantages. (JEL D23, Z13)